Imaging Features of Primary T Cell Lymphoma in Bone: A Case Report and Review of Literature - Yu, Suli; Xu, Jianqiang (Frontiers in Oncology, 2021)
Primary bone lymphoma (PBL) is a less frequent type of extranodal lymphoma, which is defined as a single skeletal tumor or multiple bone lesions without visceral or lymph node involvement. Most published cases have reported diffused large B cell lymphoma (DLBCL) of PBL, and the prognosis is good after conventional treatment. Primary T-cell lymphoma is extremely rare in the literature. The clinical symptoms, imaging findings, diagnosis, treatment and prognosis of primary T-cell lymphoma of bone are still unclear. The case details a young male patient who was treated for bone tuberculosis and was diagnosed with T-cell lymphoma during an open surgical biopsy. Further imaging evidence showed the lymphoma was localized within the femur. The patient responded poorly to combined chemo- and radiotherapy. He was confirmed with local lung metastases 11 months later and died at the 17th month of onset. I would like to provide PBL entities with some rare information about primary bone peripheral T-cell lymphoma and discuss the best strategy for the treatment of rare PBL subtypes.